2016
DOI: 10.1007/s00296-016-3499-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Egami score to predict immunoglobulin resistance in Kawasaki disease among a Western Mediterranean population

Abstract: Kawasaki disease is an acute self-limited systemic vasculitis common in childhood. Intravenous immunoglobulin (IVIG) is an effective treatment, and it reduces the incidence of cardiac complications. Egami score has been validated to identify IVIG non-responder patients in Japanese population, and it has shown high sensitivity and specificity to identify these non-responder patients. Although its effectiveness in Japan, Egami score has shown to be ineffective in non-Japanese populations. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
2
18
0
3
Order By: Relevance
“…Scoring systems have been established and validated in the Japanese population but they have some limitations. First, resistance to IVIG has not a universal definition in terms of persistence or length of reappraisal of fever, second, fever alone may not be the unique indicator of insufficient response as persistence of elevated CRP is associated also with cardiac complications, and finally those scores have not been validated outside the Japanese population [15][16][17][18][19] . We took the opportunity of the Kawanet, the widest prospective epidemiologic tool ever set up in France, a non-Asian country including multiple ethnic groups and also mixed ethnicities, to evaluate the frequency of secondary treatment after standard treatment i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scoring systems have been established and validated in the Japanese population but they have some limitations. First, resistance to IVIG has not a universal definition in terms of persistence or length of reappraisal of fever, second, fever alone may not be the unique indicator of insufficient response as persistence of elevated CRP is associated also with cardiac complications, and finally those scores have not been validated outside the Japanese population [15][16][17][18][19] . We took the opportunity of the Kawanet, the widest prospective epidemiologic tool ever set up in France, a non-Asian country including multiple ethnic groups and also mixed ethnicities, to evaluate the frequency of secondary treatment after standard treatment i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, and to our knowledge, for the first time, we observed a better performance of two of these scores in African/Afro-Caribbean patients compared to other ethnic groups, with the exclusion of Asians. Prediction of IVIg resistance is crucial to intensify initial treatment combined with IVIg to prevent cardiac complications 12,14,36,37 , but none of the currently www.nature.com/scientificreports www.nature.com/scientificreports/ published scores have good sensitivity in Caucasian populations [15][16][17][18][19]36,38 . In our multiethnic population, we identified predictive factors of IVIg resistance based on real-life practice, and built a scoring system and obtained for the first time, good sensitivity (77%) and acceptable specificity (60%) in our non-Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies, Jakob et al ( 43 ) and Sánchez-Manubens et al ( 44 ) found that IVIG resistance and the risk of developing CAAs were not assessed with Asian risk scores in German and Spanish cohorts (95% of the German cohort and 81.1% of the Spanish cohort).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, risk-scores have been developed to identify patients with a higher risk of IVIG resistance [35, 66, 106]. Unfortunately, these risk-scores do not perform adequately in Western, ethnically mixed, and in Chinese populations [24, 75, 104, 112, 115]. A possible method to decrease IVIG resistance is to intensify the initial treatment.…”
Section: Treatmentmentioning
confidence: 99%